The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1103/physrevc.87.065501
|View full text |Cite
|
Sign up to set email alerts
|

Quasielastic and multinucleon excitations in antineutrino-nucleus interactions

Abstract: We investigate the MiniBooNE recent data on the antineutrino-nucleus interaction, using the same theoretical description with the same parameters as in our previous work on neutrino interactions. The double differential quasielastic cross section, which is free from the energy reconstruction problem, is well reproduced by our model once the multinucleon excitations are incorporated. A similar agreement is achieved for the Q 2 distribution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 26 publications
7
110
0
Order By: Relevance
“…Recently, experimental [67,[113][114][115] and theoretical [24,25,[116][117][118][119][120][121][122][123][124][125][126][127][128][129] results have suggested that the chargedcurrent neutrino-nucleus scattering cross section at T2K energies could contain a significant multinucleon component. Such processes are known to be important in describing electron-nucleus scattering (for a review, see [130]), but have not yet been included in the model of neutrino-nucleus interactions in our muon neutrino disappearance analyses.…”
Section: Multinucleon Effects Studymentioning
confidence: 99%
“…Recently, experimental [67,[113][114][115] and theoretical [24,25,[116][117][118][119][120][121][122][123][124][125][126][127][128][129] results have suggested that the chargedcurrent neutrino-nucleus scattering cross section at T2K energies could contain a significant multinucleon component. Such processes are known to be important in describing electron-nucleus scattering (for a review, see [130]), but have not yet been included in the model of neutrino-nucleus interactions in our muon neutrino disappearance analyses.…”
Section: Multinucleon Effects Studymentioning
confidence: 99%
“…For the test of our theoretical model on these combinations, to avoid unnecessary errors in the following we calculate them with the real neutrinos and antineutrinos fluxes. Our present results are then the sum and the difference of our previously published neutrino [8] and antineutrino [13] and D(cos θ,E μ ) as a function of the muon emission angle, for various values of the muon kinetic energy, together with the experimental data points. Our predictions, which incorporate the multinucleon component account quite well for the data for all angles and in the full range of muon energies, both for the sum and for the difference.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We have previously tested our model on the MiniBooNE data for the differential cross sections [3,17], independently for neutrinos [8] and antineutrinos [13] reaching a good fit of the data. However in these works, the test was performed separately for the neutrinos and the antineutrinos and we did not specifically address the detailed comparison between the two.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations